Transferring the Toyota Production System into India: A Case Study - Kunju Kunju Mathew, Sagi; James, Reynold; Jones, Robert (2011)
This study argues that the success of international transference of Japanese lean manufacturing practices in general, and the Toyota Production System (TPS) in particular, is in varying degrees contingent upon the socio-cultural, historical, and environmental context of the host nations into which such transfer occurs. It contends that TPS is not simply a set of concepts, techniques, and methods that can be implemented by command and control. The specific cultural and environmental factors within Japan were central to the conceptualization, acceptance, and development of TPS in that country. In the course of transplantation of TPS practices from Japan into overseas affiliates, either an absence of due consideration, or disregard for a host nation’s unique socio-cultural and environmental factors (and the compatibility of these factors with the specific needs of TPS) could lead to unproductive organizational outcomes for the parent company. This theme is explored through an analysis of the decade-old association between the automobile industry giant Toyota Motor Corporation (TMC) Japan, and its affiliate in India, Toyota Kirloskar Motors (TKM), at Bidadi near Bangalore, India.